Adaptive Floating Fiber Embankment Technology for Tidal Flood Mitigation in Coastal Areas: A Sustainable Infrastructure Approach Toward SDG 11 and SDG 13 - Diah Agustina Prihastiwi; Syahrani Wangi Puspita (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: Coastal tidal flooding is an increasing challenge in Indonesia due to sea-level rise, land subsidence, and climate change. This study aims to evaluate the performance of floating fiber embankment technology as an adaptive infrastructure solution for tidal flood mitigation and its contribution to Sustainable Development Goals (SDGs), particularly SDG 11 and SDG 13. Method: The study used numerical simulation and laboratory experiments to analyze the structural behavior of floating fiber embankments under hydrostatic pressure. ANSYS software was applied to evaluate stress, strain, and deformation, while physical model testing was conducted to validate simulation results. Results: The results showed that the floating fiber embankment has good stability and adaptive capability. The simulation produced maximum stress of 8.231 × 10⁶ Pa, strain of 0.00045 m/m, and deformation of 0.0043 m, while laboratory testing resulted in similar values with stress of 8.210 × 10⁶ Pa, strain of 0.00044 m/m, and deformation of 0.0041 m. Novelty: The study introduces an adaptive floating fiber embankment concept as a sustainable coastal protection solution. Unlike conventional static structures, this technology can adjust to tidal changes and support climate-resilient infrastructure development aligned with SDG 11 and SDG 13.